Quantification the relationship between FITA scores and EMG skill indexes in archery - Ertan, H.; Soylu, A. R.; Korkusuz, F. (Journal of Electromyography and Kinesiology, 2005)
Forearm electromyographic (EMG) data are assumed to be an effective method in estimating performance level in archery. The aim of the current study was to establish archery skill indexes based on EMG data. Elite (n = 7, FITA score = 1303.4 ± 26.2), beginner (n = 6, FITA score = 1152 ± 9.0) and non-archers (n = 10, assumed FITA score = 250 ± 0), were involved in the study. EMG activity of Muscle flexor digitorum superficialis and Muscle extensor digitorum were quantified. Two-second periods - 1 s before and 1 s after the fall of the clicker - were used to obtain averaged and rectified EMG data. The averaged and rectified EMG data were filtered by averaging finite impulse response filter with 40 ms time window and then normalized with respect to maximum voluntary contraction. To estimate FITA scores from EMG data, the following skill indexes that based on mean area under some parts of processed EMG waveforms was offered for archery. These were the pre-clicker archery skill index (PreCASI), post-clicker archery skill index (PostCASI), archery skill index (ASI) and post-clicker archery skill index 2 (PostCASI2).The correlations between rank of FITA scores and natural logarithms of archery skill indexes were significant for log(PreCASI): r = -0.66, p < 0.0008; for log(PostCASI): r = -0.70, p < 0.0003; for log(ASI): r = -0.74, p < 0.0001; log(PostCASI2): r = -0.63, p < 0.002. It is concluded that EMG skill indexes may be useful for: (a) assessing shooting techniques, (b) evaluation of archers` progress and (c) selection of talented archers.